IMPLEMENTASI PROGRAM REHABILITASI NARAPIDANA NARKOTIKA DI LEMBAGA PEMASYARAKATAN KELAS IIB SORONG - Iriani, Eka Risko; Syauta, Novalin M; Murary, Weron (Ensiklopedia of Journal, 2025)
Implementation of the rehabilitation program for drug user prisoners in Class IIB Sorong Prison, the guidance system is in accordance with Government Regulation Number 31 of 1999 concerning Guidance and Mentoring of Narcotics Prisoners, in Sorong Prison, in essence the scope of guidance can be divided into two parts, namely: Personality guidance, and independence guidance. is Empirical Juridical, namely research that seeks to identify legal issues that exist in society with the aim of knowing other symptoms that exist in the field. The purpose of this paper is to find out the implementation of the rehabilitation program run by the Class IIB Sorong Penitentiary for narcotics convicts in Sorong City and to find out the obstacles faced in the rehabilitation program for narcotics convicts run at the Class IIB Sorong Penitentiary.The research method used in this paper is empirical juridical research. The data sources used are primary and secondary data. The data collection techniques include interviews, field observations, documentation, and literature studies. The data analysis technique used is descriptive qualitative.The results of the study, Implementation of the rehabilitation program in Class II B Sorong Prison for narcotics case inmates in Sorong City, namely, the existence of initial selection, medical rehabilitation, social rehabilitation and evaluation and monitoring and obstacles faced in the implementation of the rehabilitation program for narcotics case inmates run by Class II B Sorong Penitentiary, namely, lack of human resources, lack of budget (finance) and overcapacity of the Prison. Keywords: Implementation, Rehabilitation, Prisoners, Narcotics.